Developing the mathematics teacher workforce in England's FE colleges: towards a 'communities of practice' strategy. Issue 3 (3rd July 2022) - Dalby, Diane; Noyes, Andrew
ABSTRACT: Since policy changes in 2014 about who studies mathematics post-16 in England, the mathematics teaching workforce in further education (FE) colleges has grown and diversified. The question of how best to develop the professional practice of this changing workforce is, however, unresolved. Teachers in a recent national study report the benefits of non-formal learning but the diverse organisational structures of colleges impact on the size and focus of teacher communities and thereby the nature of professional learning. Where mathematics teachers are enabled to meet regularly or work in close proximity, teacher learning communities emerge but their development is constrained by a lack of consensus on the professional identities and competencies of mathematics teachers in FE colleges. Despite these obstacles, we argue that there is considerable potential to enhance professional learning for mathematics teachers in FE through a communities of practice approach and that such a strategy for professional development is a key component of a self-improving further education system.